The Legacy of Fatima Dudija Hatun, Sarajevo Benefactor (Prilozi za orijentalnu filologiju, 2024)
In this paper based on the available Ottoman archival sources and accessible secondary literature, an attempt is made to reconstruct the life of a Sarajevo benefactor from the end of the 18th and the first half of the 19th century, who bequeathed part of her property for religious and educational purposes.Based on the inventory of the property remained after her death, we tried to get a closer picture of the private life of a woman benefactor, then to provide information about the way and style of her life, then on the type of household furniture, textile furniture, kitchen utensils, decorative objects and other things that adorned and filled the interior of her home. Likewise, we analyzed the jewelry she owned, the style of her daily clothing, the type and quality of the materials of the clothing, and information about the rest of her movable and immovable properties. The person in case was named Fatima Dudija hatun, daughter of Pehlivan Husejn-aga, from Sarajevo, resident of Careva Mahala.